Clinical Characteristics of Parainfluenza Virus Infection among Healthy Subjects with Influenza-like Illness. (4th October 2017) - Fairchok, Mary; Chen, Wei-Ju; Mor, Deepika; Schofield, Christina; Arnold, John; Danaher, Patrick; Deiss, Robert; Lalani, Tahaniyat; Rajnik, Michael; Malone, Leslie; Grigorenko, Elena; Stalons, Donald; et al.
Abstract: Background: Parainfluenza virus (PIV) is a chief cause of croup. Less is known about the role of PIV in causing influenza-like illness (ILI) among healthy adults and children. We evaluated clinical characteristics of PIV compared with influenza (flu) infection in healthy subjects diagnosed with ILI. Methods: The Acute Respiratory Infection Consortium (ARIC) conducted an observational, longitudinal study of ILI at five US military treatment facilities from 2009 to 2016. Participants were otherwise healthy military members, retirees, and their dependents. Symptom data were captured prospectively on days 0, 3, and 7 by interview and patient diary. Nasopharyngeal specimens were collected for etiologic determination by multiplex assay (Diatherix Laboratories, LLC.) Severity scores were calculated for upper respiratory, lower respiratory, GI, composite and systemic symptoms Results: PIV did not account for a large proportion of ILI in our population with 43/961(4.7%) PIV+ vs. 153/961(15.9%) that were flu+. Age < 5 years was associated with increased detection of PIV (10% in <5 years vs. 3.2% in 5–65 years, P < 0.01). Additionally, on multivariable analysis, the presence of a child aged <5 years in the household was associated with an increased risk of PIV detection (OR = 2.58; 95% CI:1.39, 4.80). Sex, geographic location, year of detection, race/ethnicity, smoking status and obesity were all unrelated to PIV detection. Codetections occurred in 8/43 (18.6%) subjects, but codetected viruses did not show any specific pattern, with 5 different viruses found. When comparing demographic characteristics of ILI caused by flu vs. PIV, the only difference was that flu+ subjects were more often ≥5 years ( P < 0.01). Comparing symptom profile and severity of adults with PIV + ILI vs. flu+, we found no differences in the presence or severity of 20 symptoms, nor in severity scores for each of the 5 categories. Rates of hospitalization, antibiotic use, or duration of illness were also indistinguishable. Conclusion: This is one of a few studies to detail the clinical characteristics of PIV presenting as ILI in healthy subjects. PIV is more often detected in young children with ILI. Although PIV was detected 25% as often as flu, it had an indistinguishable clinical course from influenza associated ILI in adults. Disclosures: L. Malone, diatherix: Employee, Salary. E. Grigorenko, Diatherix Laboratories: Employee, Salary. D. Stalons, Diatherix Laboratories: Employee, Salary.